Dental approach and oral changes in the elderly: a literature review (Research, Society and Development, 2020)
The aging of the population requires the technical preparation of health professionals, making knowledge of the reality of the elderly population, such as oral health conditions, part of their clinical performance. Thus, the Dental Surgeon will be able to plan and execute correct and differentiated actions for this specific population group. The objective of this study was to analyze the scientific publications about the main occurrences found in the intra-buccal examination in the elderly. This work has a qualitative approach, applied nature, with the exploratory objective and bibliographic character, through the research in books, scientific journals, electronic articles, theses and dissertations that deal with the main intraocular pathological occurrences in the elderly, in the Portuguese and English, published in the years 2000 to 2020. It was also consulted literature deemed important for the subject matter, before the inclusion period. The scientific production analyzed showed the main intra-oral occurrences in the elderly population: dental loss, prosthesis use, caries disease, periodontal disease, dental wear, chewing difficulties, oral pain, xerostomia as well as soft tissue lesions of the mouth, which has some impact on the life of this population group, whether physical or psychological.